Incentives and two-sided matching: Engineering coordination mechanisms for social clouds - Christian Haas (KIT Scientific Publishing, 2014)
The Social Cloud framework leverages existing relationships between members of a social network for the exchange of resources. This thesis focuses on the design of coordination mechanisms to address two challenges in this scenario. In the first part, user participation incentives are studied. In the second part, heuristics for two-sided matching-based resource allocation are designed and evaluated.
urn:nbn:de:0072-418616
Keywords: 330; Two-Sided Matching; Social Clouds; Incentive Engineering; Social Web; Partizipation; Leistungsanreiz; Allokation; Theorie